Gas Metal Arc Welding (GMAW) Process Optimization Using Machine Learning Models - Sharaf, Ahmed (2023)
A Master of Science thesis in Engineering Systems Management by Ahmed Sharaf entitled, “Gas Metal Arc Welding (GMAW) Process Optimization Using Machine Learning Models”, submitted in November 2023. Thesis advisor is Dr. Noha Hussein. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).